A proteomics research of apoptosis of leukemia cells induced by arsenic trioxide - Wang, L.; Guo, Q.; Liu, W.; Bai, Y. (Cellular and Molecular Biology, 2017)
Leukemia is a malignant hyperplasia disease of hematopoietic system caused by a kind of hematopoietic cells detaining at a certain stage. In this study, we used HL-60 cell line to detect the effect of apoptosis induction by various concentrations of As2O3. Percentage of apoptotic cells was increased in the presence of As2O3, detected through flow cytometry. Mass spectrometric identification indicated that there were 102 differential proteins before and after intervention. Among them, expression of CH60, AT1A1, ANXA6, and EF2 increased and expression of ATPA, MYO1G, RS3 decreased. Those genes played roles in promoting HL-60 cell apoptosis induced by As2O3. This study could lay the foundation of deciphering mechanisms of HL-60 cell apoptosis and give a new possible target to the clinical application for arsenic trioxide treatment for leukemia.